Розбиття графів методом незалежних підмножин - Провотар, T.M.; Протасова, K.Д. (Доповіді НАН України, 2010)
Запропоновано метод незалежних підмножин, що дозволяє побудувати вершинні розбиття графів з контрольованими індексами підмножин розбиття. We present a method of independent subsets for vertex partitions of graphs into subsets of controlled indices. The index of a subset A of the set V of vertices of a graph Γ is the minimal number k such that, for every vertex v that belongs V, there exists a path of length ≤k from v to A.